Desain Alat Uji Impak Jatuh Bebas Untuk Pengujian Baja Struktur - Dailami Dailami; Samsul Bahri; Hamdani Hamdani (Akademi Komunitas Negeri Aceh Barat, 2020)
Abstract Impact testing is a test to measure material resistance to shock loads (dynamic). Impact testing simulates the material operating conditions often encountered when the load does not always occur slowly but rather comes suddenly. The impact test equipment to be designed in this study is a free-fall impact test. This impact test tool utilizes the mass of the object and the force of gravity. This test aims to analyze the effect of free fall impact loading on steel structures dropped from 1.5m height. The steps taken in this study include testing and data collection to determine the energy absorbed, the impact price, momentum, impulse and toughness in steel structure material when given a shock load. In this free fall impact test, weight load is at (m) = 2.4 kg with an altitude distance of (h) = 1.5m. The test results showed that the maximum absorbable energy of structural steel is at (E) = 352.94 J, the maximum impact value of structural steel at (HI) = 8.82 J / mm2, the maximum momentum of structural steel at (M) 39.04 kg.m / s and the maximum implant steel structure at (I) 39.04 Ns. Mechanical behaviour is indicated by the bending of the specimen due to impact collision (striker) when testing is done. Keywords: Free-fall impact, Structure steel __________________________ Abstrak Pengujian impak merupakan suatu pengujian untuk mengukur ketahanan bahan terhadap beban kejut (dinamis). Pengujian impak mensimulasikan kondisi operasi material yang sering ditemui dimana beban tidak selamanya terjadi secara perlahan-lahan melainkan datang secara tiba-tiba. Alat uji impak yang akan dirancang dalam penelitian ini merupakan alat uji impak jatuh bebas. Alat uji impak ini memanfaatkan massa benda serta gaya gravitasi. Pengujian ini bertujuan untuk menganalisa pengaruh pembebanan impak jatuh bebas pada baja struktur yang dijatuhkan dari ke tinggian 1,5m. Langkah yang dilakukan dalam penelitian ini meliputi pengujian dan pengambilan data untuk mengetahui energi yang diserap, harga impak, momentum, implus dan ketangguhan pada material baja struktur saat diberi beban kejut. Pada pengujian impak jatuh bebas ini, mempunyai jarak dan berat beban yaitu pada beban (m) = 2,4 kg dengan jarak ketinggian (h) = 1,5m . Dari hasil pengujian yang diperoleh energi yang diserap maksimum baja struktur (E) = 352,94 J, harga impak maksimum baja struktur (HI) = 8,82 J/mm2, momentum maksimum baja struktur (M) 39,04 kg.m/s dan implus maksimum baja struktur (I) 39,04 Ns. Perilaku mekanis ditunjukkan dengan terjadinya pembengkokan pada spesimen akibat benturan Beban (striker) saat pengujian dilakukan. Kata Kunci: Impak jatuh bebas, Baja struktur __________________________